Effectiveness of Retail Promotions in the Green Industry by Age Group: A Case Study - Hayk Khachatryan; Alicia Rihn (EDIS)
In the horticulture industry, age has frequently been used to divide and quantify gardeners (National Gardening Association, 2013).  For instance, consumers over the age of 55 account for the majority of U.S. household lawn and garden retail sales and the number of gardeners in this group is increasing (National Gardening Association, 2013).  Interestingly, young consumers are also expressing interest in gardening.  In 2012, Millennials (born after 1980) spent 78% more on gardening purchases than in the previous 2 years.  Surprisingly, men are the driving force in this age group (with a 125% increase) who spent approximately $441 per household (in 2012) with most of the expenditures being on food producing/edible plants (i.e. fruit trees, berries, vegetables and herbs).  The local and ‘grow your own food’ movements are likely the main drivers of increased interest in edible and food producing plants (National Gardening Association, 2013).  To date, research addressing retail promotions in the green industry by age segments has not been adequately addressed.